Studi Deskriptif Model Pembelajaran PAI Berbasis Lingkungan dalam Mewujudkan Visi Misi Sekolah - Auliya Hamidah Haris Poernomo; Nan Rahminawati (UPT Publikasi Ilmiah Unisba, 2022)
Abstract.The environment is nature that humans can live in. The environment is related to conditions, objects and of course, humans are included in a room which affects human life and survival. In the Qur'an, Allah says to protect the environment and not to destroy it, because humans need the environment to live. There have been many disasters caused by human activities such as throwing garbage in the wrong place resulting in flood disasters and environmental destruction. So the need for habituation and awareness of the environment inhabited by humans through education. Islamic education is that a human being is a